The new life of Baroque castles in North-Western Croatia - Botica, Dubravka (Acta historiae artis Slovenica, 2023)
The article examines the furnishing of country residences, the collecting practises and art patronage of members of two families of the old and new nobility, the Erdödy and the Vranyczány-Dobrinović, who played an important role in Croatian society and politics. The Erdödy furnished their castles in Jastrebarsko, Novi Marof and Bajnski dvori with Historicist furniture and decorated them with their collections, which consisted mainly of works of art by Old Masters. The Vranyczány followed the trend of Historicist interior decoration and expressed their personal taste more strongly, which was reflected in their estates of Mirkovec and Gornje Oroslavje, which became the centre of social gatherings of the modern Croatian art scene.
Keywords: architectural heritage; arhitekturna dediščina; art collections; Bajnski dvori; baročni gradovi; Baroque castles; Erdödy (plemiška rodbina); furnishing; krajinska arhitektura; landscape architecture; notranja oprema; Oroslavlje; prenova; renovation; umetnostne zbirke; Vranyczány (plemiška rodbina)